Dampak Teknologi dan Inovasi pada Keadilan dalam Penegakan Hukum di Era Digital - Ayu Simanjuntak; Winda Tarihoran; Lestania Simatupang; Kisah Lumban Toruan; Sri Yunita (Departement of Mathematics Education, 2023)
This research aims to investigate the impact of technology and innovation on justice in law enforcement in the digital age through the literature study method. In the ever-evolving digital age, technological developments such as big data analytics, artificial intelligence, and digital forensic technology have changed the way law enforcement operates. This research outlines the positive and negative impacts of such technologies on justice in the legal system. Study results study results show that the use of technology in law enforcement can improve the efficiency of investigations, evidence analysis, and detainee monitoring. However, there are also potential issues related to privacy and data security that need to be considered. In addition, unequal access to technology and data can also threaten justice. This research will help stakeholders in law enforcement and public policy to understand the implications of technology and innovation for justice. In addition, this study also provides a basis for future researchers to further explore these issues through more in-depth empirical research.